Frecuencia de tratamientos pulpares realizados en pacientes de 3 a 11 años de edad atendidos en el Servicio de Odontopediatría del Centro Dental Docente de la Universidad Peruana Cayetano Heredia desde enero de 2015 hasta diciembre de 2019 - Gamarra Solis, Jose Ronualdo (2021)
Background: Pulps treatments constitute one of the types of procedures most performed in pediatric patients, whose primary objective is to restore the masticatory, aesthetic and phonetic function. Objective: Determine the frequency of pulps treatments performed in patients from 3 to 11 years old treated in the Pediatric Dentistry Service at the Teaching Dental Center of the Cayetano Heredia Peruvian University from January 2015 to December 2019. Materials and Methods: A search for the medical records of patients treated in the Pediatric Dentistry service who have met the inclusion and exclusion criteria. Data were collected on age, gender, type of dentition and tooth, for the elaboration of a database, and later tables of contents. Results: From a sample of 514 virtual medical records, with 1166 pulp treatments performed, the Indirect Pulp Therapy was the most performed for both sexes, 41.17% (n = 247) for the female sex and 34.98% (n = 198) for the male sex. According to age range, 3 to 5 years old are the patients with the most Indirect Pulp Therapy performed with 39.06% (n = 359). The majority of patients with deciduous dentition underwent Indirect Pulp Therapy treatment with 39.32% (n = 326). Being the tooth mostly treated with Indirect Pulp Therapy the 84 with 41.18% (n = 70). Conclusions: The pulp treatment that was most performed within our sample was Indirect Pulp Treatment, being able to rescue that there is little attention to oral health care in patients.